Optimizing the Fulfillment of Women's Representative Rights at the Village Consultative Body (BPD) in Banyumas Regency as an Effort to Increase Women's Participation in Village Development (Gender Perspective) - Rahmah, Alef Musyahadah; Alawiya, Nayla (Jurnal Dinamika Hukum, 2022)
Women's participation in village development is still low and many are dominated by men. In fact, the support of women in Village development is the determining achievement of development done in the village. One of the women's support in village development through the representation of women in BPD membership, because BPD has a strategic role as an institution that directly faced with the community to better understand the needs of society. Departing from the fact, this article focuses on optimizing the fulfillment of women's representation in the membership of BPD, especially in Banyumas district. This research is a qualitative study with a juridical approach empirical. The field of regulation needs to be formed by Banyumas Perda of BPD which refers to Regulation of Internal Affairs Ministry number 110 year 2016 to give guarantee to women through quota 1 (one) woman in the replenishment of BPD membership. People also need to improve their legal awareness and community paradigm change about gender roles and gender relations.Keywords: BPD; optimization;  village development; women's representation